GC1qR Cleavage by Caspase-1 Drives Aerobic Glycolysis in Tumor Cells - Sünderhauf, Annika; Raschdorf, Annika; Hicken, Maren; Schlichting, Heidi; Fetzer, Franziska; Brethack, Ann-Kathrin; Perner, Sven; Kemper, Claudia; Ghebrehiwet, Berhane; Sina, Christian; Derer, Stefanie (Frontiers in Oncology, 2020)
Self-sustained cell proliferation constitutes one hallmark of cancer enabled by aerobic glycolysis which is characterized by imbalanced glycolysis and mitochondrial oxidative phosphorylation (OXPHOS) activity, named the Warburg effect. The C1q binding protein (C1QBP; gC1qR) is pivotal for mitochondrial protein translation and thus OXPHOS activity. Due to its fundamental role in ba-lan¬cing OXPHOS and glycolysis, c1qbp-/- mice display embryonic lethality, while gC1qR is ex¬ces-sive¬ly up-regulated in cancer. Although gC1qR encompasses an N-terminal mitochondrial leader it is also located in other cellular compartments. Hence, we aimed to investigate mechanisms regulating gC1qR cellular localization and its impact on tumor cell metabolism. We identified two caspase-1 clea¬vage sites in human gC1qR. GC1qR cleavage by active caspase-1 was unraveled as a cellular me-chanism that prevents mitochondrial gC1qR import, thereby enabling aerobic glycolysis and en¬hanced cell proliferation. Ex vivo, tumor grading correlated with non-mitochondrial-located gC1qR as well as with caspase-1 activation in colorectal carcinoma patients. Together, active caspase-1 cleaves gC1qR and boosts aerobic glycolysis in tumor cells.